Students’ Ability and Difficulty In Writing Narrative Text : Case Study in Junior High School In Lombok, Indonesia - Sianturi, Reni Sianturi; Zamzam, Ahmad; Susanti , Ni Wayan Mira; Thohir, Lalu (Journal of Authentic Research, 2025)
This study aims to determine the level of students’ writing ability in narrative texts and to identify the specific challenges they face in the process. The research employed a descriptive qualitative method using a case study design. Data were collected through writing tests and questionnaires, which were analyzed to assess students’ performance across five aspects of narrative writing: content, organization, grammar, vocabulary, and mechanics. The participants consisted of 30 students from Class IX.4 of SMPN 2 Sekotong, located in Sekotong District, West Lombok, Indonesia. The findings from the writing test indicated a moderate to good level of performance, with an average score of 76.76%, suggesting that students demonstrated basic proficiency in narrative composition. However, the questionnaire results, with an average response rate of 69.42%, revealed discrepancies in students’ self-perceived abilities, particularly highlighting difficulties in grammar and vocabulary usage. Prior to administering the questionnaire during the second session, the researcher clearly explained its purpose to ensure informed participation. These findings suggest that while students may perform adequately in structured writing assessments, they still face underlying difficulties in linguistic aspects of narrative writing. Practically, the results imply the need for targeted instructional support focusing on grammar and vocabulary development to improve students’ overall narrative writing skills.